1999
DOI: 10.1089/cmb.1999.6.113
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequencing With Positive and Negative Errors

Abstract: The problem addressed in this paper is concerned with DNA sequencing by hybridization. An algorithm is proposed that solves a computational phase of this approach in the presence of both positive and negative errors resulting from the hybridization experiment. No a priori knowledge of the nature and source of these errors is required. An extensive set of computational experiments showed that the algorithm behaves surprisingly well if only positive errors appear. The general case, where positive and negative er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…The greedy algorithm presented in this paper is a heuristic based on the greedy algorithm defined in [9] for the SBH problem with positive and negative errors. The original algorithm has been extended to take into consideration the information about l-mers multiplicity.…”
Section: Algorithmmentioning
confidence: 99%
“…The greedy algorithm presented in this paper is a heuristic based on the greedy algorithm defined in [9] for the SBH problem with positive and negative errors. The original algorithm has been extended to take into consideration the information about l-mers multiplicity.…”
Section: Algorithmmentioning
confidence: 99%
“…In this work we consider the optimization problem that was introduced as a model for DNA sequencing by hybridization by B lażewicz et al in [3]. In [7] it was shown that this model is N P -hard.…”
Section: Dna Sequencing By Hybridizationmentioning
confidence: 99%
“…The first approach to solve the SBH problem was a branch & bound method proposed in [3]. However, this approach becomes unpractical with growing problem size.…”
Section: Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…. m] of fragment indexes, the corresponding sequence is obtained by merging the fragments F u [1] , F u [2] , . .…”
Section: Algorithmmentioning
confidence: 99%